RANCANGAN PENGUKURAN KINERJA RANTAI PASOK BARANG PASSTHROUGH DI PT. INDONESIA NIPPON SEIKI DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD - Isnaini Agustian (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: PT. Indonesia Nippon Seiki Supply Chain Performance related to supplying Passthrough good, based on three categories, the quantity, ontime delivery and quality, the performance can not reach 100% performance. Management said that to reach perfect performance PT. INS must take high cost consequenses. There are too many factor that must be considered, so three point of view are not enough to describe the performance of the supply chain of the Passthrough goods. In this research, the writer tries to propose some Key performance indicator (KPI) based on Balanced Scorecard approach related to Supply Chain issues. All of these KPI‟s will be choosen by some management of INS as the questionaire respondent, using Analitical Hirarchy Process (AHP) and then after the proper KPI have determined the performance will be calculated and will be sumarized using Objective Matric Weighting, to get an objective analysis of the performance of Passthrough good Supply chain in PT. INS. The result of the research, there are 22 KPIs that are used to calculate the perfomace of Passthrough good Supply chain in PT. INS based on Balanced Scorecard approach. The research shows that the performance of Passthrough good Supply chain year 2012 is low but in 2013, the performance tend to be increase. PT. INS must concern to resolve the customer complaint because this KPI tend to be not good. But in generally the performance is growing better and have a lot of chances for improvement.Keywords: Performance, supply chain, Key Performance Indicator, Balanced Scorecard